The Effect of Learning Simulation Media on the Students’ Critical Thinking Skills in Vocational School during Online Learning in the Covid-19 Pandemic - Wahyudha Tri Setiyoaji; Edi Supriana; Eny Latifah; Endang Purwaningsih; Sandhi Setya Praptama (Universitas Muhammadiyah Makassar, 2021)
Critical thinking is one of the most important and necessary skills in learning physics. This study aims to determine the effect of simulation learning media on critical thinking skills during online learning. This research is a pre-experimental study with one group pre-test post-test design. This research was conducted in the even semester of the 2020/2021 academic year at the State Vocational High School 1 Grati. The sample was selected using a simple random sampling method and obtained class X TPL 1 with 30 students. The results of the pre-test and post-test data analysis showed that there was an increase in students' critical thinking skills after applying simulation media. the average result of the n-gain of students' critical thinking skills after learning using simulation media is 60.51 which is in the quite effective category. A paired t-test results show the value of sig (2-tailed) is 0.00 sig